Prognostic impact of Additional Chromosomal Abnormalities in Egyptian Chronic Myeloid Leukemia Patients - ElNahass, Yasser H.; Assem, Magda M.; Saber, Magdy M.; Abdalla, Sarah K.; Mahmoud, Hossam K.; ElRefaey, Fatma A. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Emergence of additional chromosomal abnormalities (ACAs) in chronic myeloid leukemia (CML) is associated with disease progression to advanced phases and reflects the genetic instability of CML. AIM: Is to evaluate the frequency of ACAs in chronic phase (CP) and advanced disease (AP) CML patients and study their impact on patient’s outcome, overall survival (OS) and event-free survival (EFS). RESULTS: The studied group (n = 73) included 31 males (43%) and 42 females (57%). Median age of patients at diagnosis was 37 years (17–76). Median TLC was 208×109/L (2.1–784.2), median Hb was 9.4 g/dL (5.7–13), and median platelets count was 290.5×109/L (13–1271). We identified 32 patients (44%) with ACAs. ACAs emergence was significantly associated with advanced phases of CML (13/21, 62%) compared to CP (19/52, 36%) (p = 0.048). ACAs were associated with lower median OS and EFS in CP compared to AP (38 vs. 120 ms) and (58.3 vs. 77 ms) (p = 0.026 and p = 0.065, respectively). Early molecular responders (6/17, 35%) at 3 months, and 6 months (10/26, 38%) developed ACAs less than nonoptimal responders. Disease phase, hepatomegaly and bone marrow eosinophilia were significant predictors of OS (p < 0.001, p = 0.02, p = 0.04, respectively). CONCLUSION: Early identification of ACAs in Ph+ metaphases at diagnosis and during therapy predicts CML outcome. ACAs emergence occurred at a higher frequency and at a younger age in our CML patients and are related to inferior EFS and OS.